PERBANDINGAN KEKUATAN TARIK ANTARA STRANDEDFIBERDENGAN BRAIDEDFIBERPADA FIBER REINFORCEDCOMPOSITE JENIS ULTRA HIGH MOLECULARWEIGHTPOLYETHYLENE (UHMWPE) - , PRIHASHINTA USWATUN HASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fiber reinforced composite is a material havingminimum 2 different components. The material is matrix reinforced by fiber. Fiber in FRC has many varieties in its architecture. Difference in fiber architecture can affect mechanical properties of FRC itself. Stranded fibersand braided fibers is one of the most commonly used fiber in dental practice. They have difference in fiber architecture.The aim of this study is to determine the tensile strength comparisons between stranded fibers and braided fibers inFRC type UHMWPE . This study used 8 specimens which were divided into 2 groups. Each group was made with two different fiber architectures